Domestication, breeding, omics research, and important genes of Zizania latifolia and Zizania palustris - Xie, Yan-Ning; Qi, Qian-Qian; Li, Wan-Hong; Li, Ya-Li; Zhang, Yu; Wang, Hui-Mei; Zhang, Ya-Fen; Ye, Zi-Hong; Guo, De-Ping; Qian, Qian; Zhang, Zhong-Feng; Yan, Ning (Frontiers in Plant Science, 2023)
Wild rice (Zizania spp.), an aquatic grass belonging to the subfamily Gramineae, has a high economic value. Zizania provides food (such as grains and vegetables), a habitat for wild animals, and paper-making pulps, possesses certain medicinal values, and helps control water eutrophication. Zizania is an ideal resource for expanding and enriching a rice breeding gene bank to naturally preserve valuable characteristics lost during domestication. With the Z. latifolia and Z. palustris genomes completely sequenced, fundamental achievements have been made toward understanding the origin and domestication, as well as the genetic basis of important agronomic traits of this genus, substantially accelerating the domestication of this wild plant. The present review summarizes the research results on the edible history, economic value, domestication, breeding, omics research, and important genes of Z. latifolia and Z. palustris over the past decades. These findings broaden the collective understanding of Zizania domestication and breeding, furthering human domestication, improvement, and long-term sustainability of wild plant cultivation.